Unveiling fractional vegetation cover dynamics: a spatiotemporal analysis using MODIS NDVI and machine learning - Anees, Shoaib Ahmad; Mehmood, Kaleem; Rehman, Akhtar; Rehman, Nazir Ur; Muhammad, Sultan; Shahzad, Fahad; Hussain, Khadim; Luo, Mi; Alarfaj, Abdullah A.; Alharbi, Sulaiman Ali; Khan, Waseem Razzaq (Elsevier B.V., 2024)
Understanding the dynamics of Fractional Vegetation Cover (FVC) is crucial for effective environmental monitoring and management, especially in regions like Pakistan that are sensitive to climate change. This study employs an innovative approach using MODIS NDVI data and the Pixel Dichotomy Model (PDM) to analyze the spatiotemporal dynamics of FVC across Pakistan from 2003 to 2020. Our findings reveal an overall increasing trend in FVC, with the highest value recorded in 2017 (0.37) and the lowest in 2004 (0.26). The Hurst exponent analysis (R/S ratio = 0.718) indicates a degree of long-term memory in the FVC time series. Rainfall was found to positively correlate with FVC (r = 0.6), while Land Surface Temperature (LST) and the Compounded Night Light Index (CNLI) exhibited negative correlations (r = −0.59 and r = −0.43, respectively). The Random Forest regression model highlighted CNLI as the most influential predictor (importance = 62.4%), emphasizing the need to consider human-induced factors in environmental management. These results provide critical insights for sustainable land management and contribute to understanding vegetation-climate interactions in arid and semi-arid environments."